Effectiveness of UV light as a means to reduce Salmonella contamination on tomatoes and food contact surfaces. (August 2016) - Lim, Winnie; Harrison, Mark A.
Abstract: The effectiveness of ultraviolet light at a wavelength of 254 nm to reduce Salmonella contamination on tomatoes and food contact surfaces was evaluated. Inoculated tomatoes were exposed to UV-C light at doses ranging from 0 to 223.1 mJ/cm 2 . All UV treatments significantly reduced Salmonella populations (p < 0.05). The effectiveness of UV-C light in reducing Salmonella contamination on different locations on tomato surfaces under various UV doses (0–117.2 mJ/cm 2 ) was also explored. Results indicated that regardless of the locations, UV treatment was shown to be effective in decreasing Salmonella populations. Subsequent studies evaluated possible photoreactivation or dark repair of injured Salmonella post-UV treatment. Following UV light exposure at doses of 0, 22.3, 44.6, and 89.2 mJ/cm 2, tomatoes were either exposed to visible light for 0, 3, and 5 h or stored in the dark for the same amount of time. Photoreactivation was not detected, nor was dark repair. UV light was also evaluated for its effectiveness to reduce Salmonella contamination on food contact surfaces (stainless steel, HDPE, waxed cardboard and PVC). Contaminated coupons were exposed to UV-C light at 0, 3.3, and 19.7 mJ/cm 2 . Significant differences were observed between coupons treated with UV light and the controls (p < 0.05). Coupons exposed for longer time had greater Salmonella population reductions, except for waxed cardboard coupons. Application of UV-C light to reduce Salmonella contamination in tomato handling facilities is feasible. Highlights: UV-C light was effective in reducing Salmonella contamination on tomatoes. UV-C light reduced Salmonella contamination on food contact surfaces. Photoreactivation was not evident in this study, nor was dark repair. UV-C use commercially is feasible for treating tomatoes and food contact surfaces.